2005
DOI: 10.1089/cpb.2005.8.441
|View full text |Cite
|
Sign up to set email alerts
|

Internet Accessibility and Usage among Urban Adolescents in Southern California: Implications for Web-Based Health Research

Abstract: The World Wide Web (WWW) poses a distinct capability to offer interventions tailored to the individual's characteristics. To fine tune the tailoring process, studies are needed to explore how Internet accessibility and usage are related to demographic, psychosocial, behavioral, and other health related characteristics. This study was based on a cross-sectional survey conducted on 2373 7 th grade students of various ethnic groups in Southern California. Measures of Internet use included Internet use at school o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 49 publications
2
58
0
1
Order By: Relevance
“…1 Adolescents have adopted its use extensively, integrating it into many aspects of their daily life. 2,3 As in other countries, [3][4][5] the vast majority of 14-to 19-year-olds in Switzerland have reported using the Internet several times per week. 6 The growing importance of the Internet for adolescents has gradually led health professionals to examine the health implications associated with this activity.…”
mentioning
confidence: 91%
“…1 Adolescents have adopted its use extensively, integrating it into many aspects of their daily life. 2,3 As in other countries, [3][4][5] the vast majority of 14-to 19-year-olds in Switzerland have reported using the Internet several times per week. 6 The growing importance of the Internet for adolescents has gradually led health professionals to examine the health implications associated with this activity.…”
mentioning
confidence: 91%
“…In relation to users' psychological profile, studies have revealed a correlation between depression, locus of control, loneliness, social anxiety, self-esteem and Internet addiction (Selfhout et al, 2009;Sun et al, 2005). Whang et al (2003) found that Internet addicts had a higher degree of loneliness and depression compared to non-addicts.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have generally found an hourly increment in TV-viewing is correlated with more adverse mental health outcomes, such as anxiety, depression, and attention deficits and problems in cognition in children [5] [14] [15]; whereas the effects of computer and internet use are still unclear. Some have found correlations between internet use and increased likelihood of depression in both adults and 6 th -grade students [16] [17]; some found the opposite effects [18]; and others have found null relationships [19]. Therefore, more research is needed to firmly establish the association between internet use and well-being.…”
Section: Meaning (M) and Accomplishment (A) These Aspects Have Eachmentioning
confidence: 99%